Concentration‐dependent cellular behavior and osteogenic differentiation effect induced in bone marrow mesenchymal stem cells treated with magnetic graphene oxide. Issue 1 (6th September 2019) - He, Yi; Li, Yiming; Chen, Guanhui; Wei, Changbo; Zhang, Xiliu; Zeng, Binghui; Yi, Chen; Wang, Chao; Yu, Dongsheng
Abstract: The scaffold‐free cell sheet plays an important role in stem‐cell‐based regeneration. Graphene oxide (GO) endows nanoparticles (NPs) with special characteristics and therefore has attracted increasing attention in recent years. However, the existence of toxicity in GO and its derivatives limits their ability to promote osteogenic differentiation. Magnetic graphene oxide (MGO), a novel combination of Fe3 O4 and GO with diverse unique properties, has not been studied in bone tissue engineering. In this study, MGO was fabricated, and the previously undiscovered relationships—including cellular behavior and the effects of osteogenic differentiation and related mechanisms of MGO in rat bone‐marrow‐derived mesenchymal stem cells (BMSCs)—were investigated for the first time. Here, we found that MGO was not only biocompatible at low concentrations, but also could significantly accelerate osteogenic differentiation in BMSCs. Both the cellular behavior and bone‐formation differentiation in BMSCs treated with MGO showed concentration‐dependent characteristics. In addition, the regulation of osteogenic differentiation in BMSCs treated with MGO might be involved with the Wnt/β‐catenin and BMP signaling pathways. Furthermore, MGO demonstrated a better ability for osteogenic differentiation in BMSCs than did GO. The current work indicated a significant use for MGO nanocomposite scaffolds in biocompatibility and bone regeneration, which could provide new insight into bone regeneration in the future.